Pengaruh Citra Destinasi, E-WOM, Terhadap Kepuasan Wisatawan dan Kepercayaan: Studi pada Wisatawan yang Berkunjung Tebing Breksi Daerah Istimewa Yogyakarta - Devi Aprilia S; Eni Endah Pujiastuti; Lukmono Hadi (Prodi Manajemen Fakultas Ekonomi dan Bisnis Universitas Islam Raden Rahmat Malang, 2019)
The purpose of trying to make the uniqueness of tourism products is to be able to attract tourists to visit and have future behavioral intentions. Therefore this study aims to examine the influence of destination image variables, e-wom on satisfaction and trust. The problem raised is whether the Destinastion Image has a significant effect on Tourist Satisfaction? Does E-WOM have a significant effect on the Tourist System? Is the Image Objective Significant to Trust? Does E-WOM have a significant effect on Trust? Research is conducted on tourists who visit the tourist attraction of Tebing Breksi DI Yogyakarta. The number of samples used was 115 people using systematic random sampling. Analysis techniques using SEM. The results showed that the Destinastion Image had a significant effect on Tourist Satisfaction, E-WOM had a significant effect on Tourist Satistfacton, Destination Image had a significant effect on Trust, E-WOM had a significant effect on Trust, Tourist Satisfaction had a significant effect on Trust.